MAGICAL GIRL IN KELLY BARNHILL’S THE GIRL WHO DRANK THE MOON - Yenni Shintia; Abu Fanani (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
This article is the study of magical girl in the novel using magic theory and descriptive qualitative as the method. Through such a method, the researcher analyzes and describes the words and the author’s description regarding magical girl in the novel; Luna’s childhood that is full of magical life, the elements of fantasy potrayed in the novel, andcomparison of Luna’s magic to Xan’s magic. The finding is that Luna as the main character learning magic from her foster parent, Xan, is really a magical girl since her magic is stronger than her teaching foster parent, Xan, the witch. Besides, the elements of fantasy shows magical situation in which Luna lives.